2001
DOI: 10.1117/12.450575
|View full text |Cite
|
Sign up to set email alerts
|

<title>Recent x-ray laser experiments on the COMET facility</title>

Abstract: The development of the transient collisional excitation x-ray laser scheme using tabletop laser systems with multiple pulse capability has progressed rapidly in the last three years. The high small-signal gain and strong x-ray output have been demonstrated for laser drive energies of typically less than 10 J. We report recent x-ray laser experiments on the Lawrence Livermore National Laboratory (LLNL) Compact Multipulse Terawatt (COMET) tabletop facility using this technique. In particular, the saturated outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Using these interferometers, they observed the dynamics of high-density plasmas. Using a transient collisional excitation type nickel-like palladium soft x-ray laser at the wavelength of 14.7 nm, Dunn et al (2001) have demonstrated Mach-Zender type interferometer using gratings as beam splitters, which is shown schematically in figure 59. A line-focused laser produced cylindrical plasma was probed by a few ps x-ray laser pulse, resulting in good interferograms as shown in figure 60.…”
Section: Soft X-ray Laser Interferometersmentioning
confidence: 99%
“…Using these interferometers, they observed the dynamics of high-density plasmas. Using a transient collisional excitation type nickel-like palladium soft x-ray laser at the wavelength of 14.7 nm, Dunn et al (2001) have demonstrated Mach-Zender type interferometer using gratings as beam splitters, which is shown schematically in figure 59. A line-focused laser produced cylindrical plasma was probed by a few ps x-ray laser pulse, resulting in good interferograms as shown in figure 60.…”
Section: Soft X-ray Laser Interferometersmentioning
confidence: 99%
“…With increasing prepulse amplitude the modulations of the far-field showed a tendency to become weaker and more irregular. The angular frequency and the modulation depth are considerably lower compared to the interference fringes observed in the far-field beam patterns of [11,12].…”
mentioning
confidence: 69%
“…Total energy in the two beams is of order 3 -7 J to produce lasing where the peak-to-peak delay between the laser pulses is found to be optimal at 700 ps with the short pulse arriving after the long pulse. High photon flux/shot, high monochromaticity, and short pulse duration when combined with small source area and beam divergence properties of the 14.7 nm line [14] give ultra-high peak brightness ~ 10 25 ph. mm -2 mrad -2 s -1 (0.1% BW) -1 assuming a 2 ps pulse duration.…”
Section: Methodsmentioning
confidence: 99%